2023
DOI: 10.32604/iasc.2023.031838
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Inclined Tension Crack on Rock Slope Stability by SSR Technique

Abstract: The tension cracks and joints in rock or soil slopes affect their failure stability. Prediction of rock or soil slope failure is one of the most challenging tasks in the earth sciences. The actual slopes consist of inhomogeneous materials, complex morphology, and erratic joints. Most studies concerning the failure of rock slopes primarily focused on determining Factor of Safety (FoS) and Critical Slip Surface (CSS). In this article, the effect of inclined tension crack on a rock slope failure is studied numeri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 28 publications
0
2
0
Order By: Relevance
“…The slope model comprises a total of 3382 elements and 6879 nodes. Additional details on the study, specifically the impact of an inclined TC on slope stability can be found in our prior paper 5 . The RS2 software is employed to ascertain the Critical Strength Reduction Factor (CSRF) and identify the CSS of the slope.…”
Section: Development Of Slope Model and Characterisation Of Rock Mass...mentioning
confidence: 99%
See 1 more Smart Citation
“…The slope model comprises a total of 3382 elements and 6879 nodes. Additional details on the study, specifically the impact of an inclined TC on slope stability can be found in our prior paper 5 . The RS2 software is employed to ascertain the Critical Strength Reduction Factor (CSRF) and identify the CSS of the slope.…”
Section: Development Of Slope Model and Characterisation Of Rock Mass...mentioning
confidence: 99%
“…Ramana et al, 5 recently conducted a numerical study examining the impact of the inclination angle of a tension crack on the stability of a rock slope. Their findings revealed that the FoS initially increases with the inclination angle of the tension crack until it reaches a constant value.…”
mentioning
confidence: 99%